Measuring the effectiveness of a fatigue and breathlessness group for palliative patients. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Brookes, Katie; Edwards, Anne; Marshall, Samantha; Williams, Sarah
Abstract : Background: It has long been known that fatigue and breathlessness for patients with a life limiting illness is prevalent and is frequently rated as having a greater impact on quality of life than pain (Hoekstra et al 2007). It has also been shown that often it is not addressed adequately, (Coakley et al 2002). Patients believe that the symptoms are an inevitable part of their disease and patient, carers and some health professionals misguidedly use rest as a coping strategy. In 2007, in order to address these issues in a group setting, the first Fatigue and Breathlessness course commenced at St Peter's Hospice, Bristol. Topics covered on the course are fatigue, breathlessness, benefits of exercise, energy conservation, sleep, anxiety management and nutrition. Patients themselves set goals, and are encouraged to practise what they have learnt in the group at home. One of the biggest challenges has been how to measure the effectiveness of the programme. As highlighted by Pearson et al (2007) 'this poses significant problems in palliative care due to the declining function of clients that confounds the apparent effectiveness of the intervention'. An assessment tool has now been introduced which asks patients to measure their symptoms using a visual analogue scale (VAS), alongside a questionnaire which gives a qualitative assessment of abilities and focuses on goal achievement. Aim: To measure the effectiveness of the course using pre and post VAS scores and qualitative assessment tools such as goal setting and questionnaires. Conclusion: Goal setting and patient feedback proved to be the most effective tools in providing measurable and meaningful outcomes. This demonstrated a high patient satisfaction rate and improvement in quality of life. We can now provide evidence for the effectiveness of the course in a palliative setting.